ECONOMIC ANALYSIS OF THE EFFECTIVENESS OF EXISTING TOOLS OF STATE SUPPORT FOR AGRO-INDUSTRIAL COMPLEX OF THE REGION - Yuriy Bugay (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2018)
The work is devoted to the evaluation of the effectiveness of existing tools of state support for the development of the agro-industrial complex of the region (the case of the Altai Region). The purpose of the study is to develop a method for determining the appropriateness and effectiveness of the existing tools of state support. The author’s understanding of the essence and structure of tools of state support for agricultural production is presented in the work. On the basis of empirical data, an analysis of the application of these instruments, directions and measures of state support to agriculture is carried out with the use of the data of the Altai Region as one of the leading agrarian-oriented territories of Russia. It is established that the most significant and effective tool of state support for the agro-industrial complex of the region is “providing unrelated support to agricultural producers in the field of crop production”. The author reveals the features of granting subsidies per 1 hectare of agricultural crops in the region, taking into account the specifics of agricultural production, due to different climatic conditions. The analysis of the practice of subsidizing the Altai Region on the basis of indicators of the hydrothermal coefficient makes it possible to conclude that the state agrarian policy at the level of the region under study is effective, because its measures help to level the conditions for profitable behavior of the agrarian business for commodity producers operating in different natural and climatic conditions. Based on the analysis, a conclusion is made about the effectiveness of state support in the region, but at the same time it is noted that in order to further improve the mechanism for implementing the agrarian policy of the Altai Region, it is necessary to establish a basic price for the main types of agricultural products as an indicative planning tool, and not only direct, but also other types of financing of the agro-industrial complex.